The Correlation Between Parents’ Motivation and Students’ Learning Achievement on The Subject of Islamic Education And Attitudes in Grade VIII at SMP Muhammadiyah 2 Bojonegoro - Su taji; Zainuddin Maliki (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study is aimed to explore whether the parents’ motivation influences the students’ learning outcomes of Islamic education in grade VIII at SMP Muhammadiyah 2 Bojonegoro. Does the parents’ motivation affect the attitudes of students of grade VIII at SMP Muhammadiyah 2 Bojonegoro. How is the correlation between the parents’ motivation and the students learning outcomes on Islamic education and attitudes of students of grade VIII at SMP Muhammadiyah 2 Bojonegoro. This is a descriptive quantitative research. Types of descriptive research is based on the results of data analysis of the fundamental answer about the correlation between dependent variables and independent variables by analyzing the variables of occurrence or the emergence of certain phenomena described. While the methods used in data collection are observation, questionnaires, and documentation. Data analyst technique used are statistical method kolmogorov smirnov and ANOVA two laned. The findings of this study is concluded that from the results of statistical analysis using one path ANOVA with SPSS calculation, for the first hypothesis test found the price of F count is 31,596 and the significance is 0.000, then H1 is accepted and Ho is rejected. So, the motivation to study affects the students’ learning outcomes of Islamic education of students in grade VIII at SMP Muhammadiyah 2 Bojonegoro. Keywords: Parents’ motivation toward the learning outcomes, Islamic education and attitudes